MIRAGRODEP Model - International Food Policy Research Institute (International Food Policy Research Institute, 2011)
MIRAGRODEP is a global Computable General Equilibrium (CGE) model based on MIRAGE (Modelling International Relations under Applied General Equilibrium). The model was developed and improved with the support of The African Growth and Development Policy Modeling Consortium (AGRODEP). It is a multi-region, multi-sector, dynamically recursive CGE model. MIRAGE was initially developed at CEPII and was devoted to trade policy analysis; this original model was used at IFPRI prior the development of the MIRAGRODEP version and continues to be used in CEPII (France) and by various international and academic institutions around the world. The core MIRAGRODEP model is an open-source resource distributed by the AGRODEP network, with training sessions held periodically to teach researchers how to use the model.